Catheter-associated Urinary Tract Infections in a trauma care facility in India: trend over ten years - Ningombam, Aparna; Thakur, Arpan Kumar; Srivastava, Ashish Kumar; Varma, Sharin; Kirti, Madhavi; Ahmed, M. Nizam; Tluanpuii, Vanlal; Soni, Kapil Dev; Aggarwal, Richa; Singh, Gyanendra Pal; Bindra, Ashish; Sokhal, Navdeep; et al. (The Journal of Infection in Developing Countries, 2025)
Introduction: Catheter-associated urinary tract infections (CAUTIs) are one of the most common device-associated infections acquired in a hospital. Trauma patients are highly susceptible to CAUTI, as catheterization is a lifesaving measure often required for their management. This study focuses on the profile of CAUTI, the organism profile with antibiotic susceptibility patterns, and the clinical outcomes in the ICUs of a trauma care center. Methodology: A retrospective analysis of prospective surveillance data of patients in ICUs was done over a period of ten years (2010-2019) in a level 1 trauma center. A modified NHSN definition of CAUTI was used. Microbiological processing and antibiotic susceptibility profile was done based on standard guidelines. Clinical outcomes were considered for analysis. Results: A total of 10,732 patients were included in the study, accounting for 98,131 patient days and 78,126 urinary catheter days (UCD). Among 546 patients, 577 episodes of CAUTI were recorded, giving a CAUTI rate of 7.4/1,000 catheter days. The average length of stay (LOS) of patients was 19.9 days. There was a significant relationship between UCD and the development of CAUTI. Orthopedic and spinal injuries (91%) accounted for the maximum device utilization ratio, followed by polytrauma (90%), miscellaneous injuries (88%), and head injuries (69%). CAUTI episodes were the highest in head injury patients. Gram-negative organisms (53.4%) dominated the pathogen profile. The crude mortality was 25.1%. Conclusions: Surveillance of CAUTI with analysis of the organisms and the antibiotic susceptibility trend will help improve infection prevention practices and antibiotic stewardship programs in local hospital settings.